Mitral and tricuspid annulus disjunction frequently coexist. (14th October 2021) - Aabel, E; Chivulescu, M; Dejgaard, L A; Ribe, M; Gjertsen, E; Hopp, E; Hunt, T E; Lie, O H; Haugaa, K H
Abstract: Background: Mitral annulus disjunction (MAD) is an abnormal atrial displacement of the mitral annulus, frequently found in patients with high-risk arrhythmogenic mitral valve prolapse syndrome. It is unknown whether the annulus disjunction extends to the right side of the heart as tricuspid annulus disjunction (TAD), and whether it is associated with right ventricular electrical instability. Purpose: We aimed to explore the presence of TAD, and if extended annulus disjunction was associated with ventricular arrhythmias. Methods: We included patients with previously described MAD assessed by cardiac magnetic resonance imaging (CMR) in an ambispective cohort study. MAD and TAD was defined as ≥1 mm separation between the respective atrial wall-valve leaflet junction and the top of the ventricular myocardium. TAD was assessed in the lateral and inferior right ventricular free wall by means of the 4-chamber and right ventricular 2-chamber views, respectively. MAD circumference was assessed by a CMR study protocol with six left ventricular long axis views separated by 30 degrees. Mitral valve prolapse was defined as ≥2 mm superior displacement of any part of the mitral leaflets beyond the mitral annulus. Ventricular arrhythmias were defined as aborted cardiac arrest or non-sustained/sustained ventricular tachycardias recorded by electrocardiogram (ECG), stress ECG or Holter monitoring. Results: We included 92 patients with MAD (62% female, age 47±16 years, 71% mitral valve prolapse). TAD was found in 48 (52%) patients, both in the lateral (n=40, 83%) and inferior (n=30, 63%) right ventricular free wall. Patients with TAD were older (age 51±16 years vs. 43±14 years, p=0.01), had greater MAD circumference (168±56° vs. 117±62°, p=0.001) and greater MAD distance (9.2±2.9 mm vs. 6.4±2.8 mm, p<0.001). Additionally, patients with TAD had more frequently mitral valve prolapse (40 patients [85%] vs. 25 patients [57%], p=0.003), whereas similar frequency of bileaflet prolapse (17 patients [39%] vs. 10 patients [39%], p=0.99). Ventricular arrhythmias had occurred in 38 (41%) patients, who were younger (age 40±14 years vs. 52±15 years, p<0.001) and had less frequently TAD (14 patients [37%] vs. 34 patients [63%], p=0.01; univariate odds ratio 0.34 [0.15–0.81], p=0.02). However, TAD was not associated with ventricular arrhythmias when adjusted for age (multivariate odds ratio 0.46 [0.18–1.15], p=0.10). Conclusions: TAD by CMR was highly prevalent in patients with MAD and was a marker of severe annulus disjunction and mitral valve prolapse. TAD was not associated with more ventricular arrhythmias. This novel marker warrants further research to explore the clinical implications of right-sided annulus disjunction. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Norwegian Research Council